2023
DOI: 10.1021/acs.jafc.2c09085
|View full text |Cite
|
Sign up to set email alerts
|

Effective Extraction of Bisphenol Compounds from Milk with Stable Zr(IV)-Based Metal–Organic Framework Particles

Abstract: Bisphenol compounds (BPs) have recently been the subject of growing interest due to their wide use in industrial and consumer products. Besides their adverse effects on human endocrine system, effective extraction of BPs and their elimination from complex sample matrix are still significant challenges in food analysis. Herein, a novel Zr(IV)-based metal−organic framework (MOF), named BUT-16, has been synthesized and utilized for the extraction and enrichment of BPs in milk samples. Bisphenol A (BPA), one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…4,5 Dietary ingestion from these potentially hazardous chemicals is considered as the primary route of exposure to threaten human health. 6−8 Over the past decades, although some techniques with gas chromatography−mass spectrometry (GC-MS), 9 liquid chromatography−mass spectrometry (LC-MS), 10 and high-performance liquid chromatography (HPLC) 11 were developed for the detection of TBBPA and TBBPS, there were still shortcoming and limitations due to their complex sample preparation procedures, time-consuming analysis, and high organic solvent amount. Therefore, it is necessary to establish a sensitive and rapid approach for the detection of TBBPA and TBBPS in food samples.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Dietary ingestion from these potentially hazardous chemicals is considered as the primary route of exposure to threaten human health. 6−8 Over the past decades, although some techniques with gas chromatography−mass spectrometry (GC-MS), 9 liquid chromatography−mass spectrometry (LC-MS), 10 and high-performance liquid chromatography (HPLC) 11 were developed for the detection of TBBPA and TBBPS, there were still shortcoming and limitations due to their complex sample preparation procedures, time-consuming analysis, and high organic solvent amount. Therefore, it is necessary to establish a sensitive and rapid approach for the detection of TBBPA and TBBPS in food samples.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Tetrabromobisphenol A (TBBPA) and tetrabromobisphenol S (TBBPS), served as the class of brominated flame retardants (BFRs), have been widely utilized with additives in various products containing polycarbonate plastics; according to an annual output, more than 100,000 tons have been used. However, it is reported that even low levels of TBBPA and TBBPS can disrupt the endocrine system, affect neurobehavioral function, damage the liver, etc. , Dietary ingestion from these potentially hazardous chemicals is considered as the primary route of exposure to threaten human health. Over the past decades, although some techniques with gas chromatography–mass spectrometry (GC-MS), liquid chromatography–mass spectrometry (LC-MS), and high-performance liquid chromatography (HPLC) were developed for the detection of TBBPA and TBBPS, there were still shortcoming and limitations due to their complex sample preparation procedures, time-consuming analysis, and high organic solvent amount. Therefore, it is necessary to establish a sensitive and rapid approach for the detection of TBBPA and TBBPS in food samples.…”
Section: Introductionmentioning
confidence: 99%